Development of communication media, information, and education on safe, comfortable, and healthy bicycle movements - Prayogi Dwina Angga; Deddy Whinata Kardiyanto (Journal Of Sport Education (JOPE), 2024)
(English)This research and development aim to produce communication, information and education media products for safe, comfortable and healthy bicycle movements. The research and development approach for educational media posters and leaflets adapts the stages of research and development by Borg and Gall which outlines 4 stages, namely: (1) preliminary study; (2) planning and development; (3) validation, evaluation and revision; (4) implementation. This research and development was carried out in Malang city and Solo city using the target target bicycle community. Data analysis techniques used in research and development use qualitative and quantitative approaches. Qualitative data is obtained from the results of open questions. Quantitative data is obtained through the results of filling out questionnaires conducted in expert validation tests, small group trials and large group trials. The results of the validation test conducted by material experts and media experts obtained a percentage of 86% and 83.13% respectively. The results of the small group trial obtained a percentage value of 89.19%, while in the large group trial obtained a percentage value of 89.30%. All the results of testing the product both at the validity and practicality test stages have very good criteria. It is hoped that this media will become an instrument that can increase knowledge and change the behavior of communities or individuals by implementing cycling behavior properly and correctly. (Indonesian)Penelitian dan pengembangan ini bertujuan untuk menghasilkan produk media komunikasi, informasi dan edukasi gerakan sepeda aman, nyaman dan sehat. Pendekatan penelitian dan pengembangan media edukasi poster dan leaflet ini mengadaptasi tahapan penelitian dan pengembangan oleh Borg dan Gall yang secara garis besar terdapat 4 tahapan, yaitu: (1) studi pendahuluan; (2) perencanaan dan pengembangan; (3) validasi, evaluasi dan revisi; (4) implementasi. Penelitian dan pengembangan ini dilaksanakan di kota Malang dan kota Solo dengan menggunakan target sasaran komunitas sepeda. Teknik analisis data yang digunakan dalam penelitian dan pengembangan menggunakan pendekatan kualitatif dan kuantitatif. Data kualitatif diperoleh dari hasil pertanyaan terbuka. Data kuantitatif diperoleh melalui hasil pengisian angket yang dilakukan pada uji validasi ahli, uji coba kelompok kecil dan uji coba kelompok besar. Hasil uji validasi yang dilakukan oleh ahli materi dan ahli media diperoleh persentase berturut-turut sebesar 86% dan 83.13%. Pada hasil uji coba kelompok kecil diperoleh nilai persentase sebesar 89.19%, sedangkan pada uji coba kelompok besar diperoleh nilai persentase sebesar 89.30%. Seluruh hasil pengujian terhadap produk baik pada tahap uji validitas maupun kepraktisan memiliki kriteria sangat baik. Adanya media ini diharapkan menjadi salah satu alat yang dapat meningkatkan pengetahuan, serta dapat merubah perilaku komunitas atau individu dengan menerapkan perilaku bersepeda secara baik dan benar. Copyright © The Author (s) 2024Journal of Sport Education (JOPE) is licensed under a Creative Commons Attribution-ShareAlike 4.0 International License.